Education today: 12 + 5 < 4 - lessons of education reforms in Portugal and beyond - Khmelinskii, Igor (2019)
Since the adoption of the ‘Lei de Bases…’ of 1984, the quality of education in Portugal is declining, undermined by ‘critical, creative and independent thinking’, implemented by neglecting memorization as a learning tool, as supposedly students should understand things without knowing them. As a consequence, vast majority of students can’t retain any abstract knowledge. They prepare from scratch for their tests and forget everything afterwards. The students never acquire essential primary-school skills such as capacity to do mental calculations, hence the title of this report, comparing contemporary school + university education to pre-1984 primary school of 4 years. The quality of education is further degraded by ‘evaluation’ of teachers at school and university, judged by academic success and degree of satisfaction of their students. With the students objectively incapable to learn, understand or remember, the teachers have a dilemma of either letting such students pass without retained knowledge, skills and competences, or else have their own ‘evaluation’ suffer. As the generations change, students who were ‘passed’ become teachers themselves, still with no retained knowledge and thus no moral authority to fail their own students. Thus, the level of requirements monotonously degrades, with the educational fraud perpetuated in the new generations.